The use of cell-mediated immunity for the evaluation of influenza vaccines: an upcoming necessity - E Gianchecchi; A Torelli; E Montomoli (Taylor & Francis Group, 2019)
Influenza vaccines are a fundamental tool for preventing the disease and reducing its consequences, particularly in specific high-risk groups. In order to be licensed, influenza vaccines have to meet strict criteria established by European Medicines Agency. Although the licensure of influenza vaccines started 65 years ago, Hemagglutination Inhibition and Single Radial Hemolysis are the only serological assays that can ascertain correlates of protection. However, they present evident limitations. The present review focuses on the evaluation of cell-mediated immunity (CMI), which plays an important role in the host immune response in protecting against virus-related illness and in the establishment of long-term immunological memory. Although correlates of protection are not currently available for CMI, it would be advisable to investigate this kind of immunological response for the evaluation of next-generation vaccines.